2013
DOI: 10.1186/2049-6958-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutraceutical diet integration, with coenzyme Q10 (Q-Ter multicomposite) and creatine, on dyspnea, exercise tolerance, and quality of life in COPD patients with chronic respiratory failure

Abstract: BackgroundThe protein-calorie malnutrition, resulting in muscle mass loss, frequently occurs in severe COPD patients with chronic respiratory failure (CRF), causing dyspnea, reduced exercise tolerance and impaired quality of life.The cause of this occurrence is an intake-output energy imbalance. A documented deficit of phosphocreatine and reduced mithocondrial energy production can contribute to this imbalance.Aim of this study is to verify whether a dietary supplementation with creatine and coenzyme Q10, impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 67 publications
1
26
0
2
Order By: Relevance
“…15 Previous studies have reported L-carnitine 16 and Q10 15-17 as potent antioxidants, each having a positive effect on QoL. L-carnitine plays an important role in energy production in the myocardium and inhibits fatty acid ester reposition that occurs during ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies have reported L-carnitine 16 and Q10 15-17 as potent antioxidants, each having a positive effect on QoL. L-carnitine plays an important role in energy production in the myocardium and inhibits fatty acid ester reposition that occurs during ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional defi ciency and negative energy balance are common among patients hospitalized with COPD, particularly during acute exacerbations, [17][18][19] and have been associated with poor prognoses. [20][21][22] Not surprisingly, growing evidence suggests that nutritional interventions such as vitamin D repletion, 23,24 dietary fi ber, 25,26 and oral nutritional supplementation (ONS) [27][28][29] are associated with improved outcomes for patients with COPD on a variety of dimensions. In particular, ONS use is associated with improvements in weight gain, lean body mass, muscle strength, 6-min walking distance, and ability to exercise in patients with COPD.…”
mentioning
confidence: 99%
“…Notably, confirmations come from biopsies of the muscles, which showed alterations in the number and function of mitochondria [82,83]. Also, it is reported that in chronic diseases, such as COPD, there could be a deficit of elements such as coenzyme Q10 or ubiquinone that are essential for the production of ATP and energy by mitochondrion promotion [84][85][86].…”
Section: Disease and Nutritionmentioning
confidence: 91%
“…A nutraceutical can be defined as a dietary fortified supplement that may provide health benefits in addition to its basic nutritional value [84], delivered for therapeutic purposes in a higher concentration than what is available from a normal diet. Several studies have been addressed to modulate muscle protein synthesis and energy state in COPD patients.…”
Section: Nutrition and Dietary Supplements Could Affect Microbiota Dymentioning
confidence: 99%